Expressions of Austronesian thought and emotions - Fox, James J., 1940- (Comparative Austronesian series., 2018)
This is a volume intended for the Comparative Austronesian Series. It consists of six essays on conceptions of thought and the emotions based on extended field research by recognized senior anthropologists. The essays deal with six different Austronesian-speaking societies covering an area from Sumatra to the island of Dobu in Melanesia. The volume is thus methodologically constructed to encompass both the western and eastern Austronesian world. The introduction to the volume situates these studies within an anthropological and linguistic literature to which these studies offer an important contribution. This volume continues theoretical work already published in Comparative Austronesian series, a series which was begun in the 1990s as a major interdisciplinary initiative at The Australian National University.